FXR activation protects against NAFLD via bile-acid-dependent reductions in lipid absorption - Clifford, Bethan L.; Sedgeman, Leslie R.; Williams, Kevin J.; Morand, Pauline; Cheng, Angela; Jarrett, Kelsey E.; Chan, Alvin P.; Brearley-Sholto, Madelaine C.; Wahlström, Annika; Ashby, Julianne W.; Barshop, William; Wohlschlegel, James; et al. (Cell metabolism, 2021)
FXR agonists are used to treat non-alcoholic fatty liver disease (NAFLD), in part because they reduce hepatic lipids. Here, we show that FXR activation with the FXR agonist GSK2324 controls hepatic lipids via reduced absorption and selective decreases in fatty acid synthesis. Using comprehensive lipidomic analyses, we show that FXR activation in mice or humans specifically reduces hepatic levels of mono- and polyunsaturated fatty acids (MUFA and PUFA). Decreases in MUFA are due to FXR-dependent repression of Scd1, Dgat2, and Lpin1 expression, which is independent of SHP and SREBP1c. FXR-dependent decreases in PUFAs are mediated by decreases in lipid absorption. Replenishing bile acids in the diet prevented decreased lipid absorption in GSK2324-treated mice, suggesting that FXR reduces absorption via decreased bile acids. We used tissue-specific FXR KO mice to show that hepatic FXR controls lipogenic genes, whereas intestinal FXR controls lipid absorption. Together, our studies establish two distinct pathways by which FXR regulates hepatic lipids. [Display omitted] •Non-steroidal agonists of FXR significantly decrease intestinal lipid absorption•FXR decreases hepatic triglycerides independently of SHP and SREBP1C•FXR activation reduces expression of three key lipogenic genes, Scd1, Lpin1, and Dgat2•Intestinal and hepatic FXR are both required to decrease hepatic triglycerides The nuclear receptor FXR lowers hepatic triglycerides to protect against the onset of NAFLD. Clifford et al. demonstrate that activation of FXR decreases hepatic triglycerides through two distinct mechanisms. First, via bile-acid-dependent decreases in intestinal lipid absorption and second, through selective changes in lipogenesis.